GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN BUDAYA ORGANISASI SEBAGAI DETERMINAN KINERJA KARYAWAN (Studi Empiris pada KPP Pratama Pare) - Dwi Anggardini Sulistiyorini (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
The purpose of this research is to investigate the efects of leadership style, motivation and corporate culture on employee performance. Using these variables, for instance Chatman and Bersade (1997), She (1999), Abdul Rashid (2003) and Yammarino et al., (1993) discovered efect corporate culture and leadership style toward job satisfaction to increase employee’s performance. The study was conducted at KPP Pratama Pare, the sample size is about 102 employee, using the linier regression analysis. The results show that leadership style, motivation, corporate culture has positive significance efect on employee performance. The efect of leadership style on employee performance is positive significant; The efect of motivation on employee performance is positive significant; The efect of corporate culture on employee performance is positive significant; The efect of corporate culture style on employee performance as dominant.